Teaching competencies required for the teaching of geography in the middle stage - Salam Jaber, Hussam (Journal of College of Education, 2019)
The importance of this research is to develop the professional and educational performance of the teachers of geography in the middle stage and to update their preparation programs more effectively.This study attempts to determine the teaching competencies necessary for teachers and the level of importance in the development of their professional and scientific performance and their progress towards a better future to achieve an effective level. Accordingly, the research community was determined, which consisted of the middle schools for girls of the morning of the Directorate General of Education Baghdad Karkh / third. As for the research tool, the researcher adopted the descriptive approach. In order to verify the results of the research, the researcher used the following statistical methods: - Weighted mean, percentage weight, Pearson correlation coefficient, T test, analysis of variance. The most important results are: Some of the teaching competencies of the research sample achieved a high degree in the level of verification, and according to the fields set.